The practices of regression testing in the electronic services flagship application (eServices) / Noorzliana Ahmad - Ahmad, Noorzliana (2006)
Malaysian government initiatives e-Government to push the country into information communication and technology (ICT) era with a vision to improve government internal operations. With e-Govemment electronic services citizens are able to exploit internet technology to improve convenience, accessibihty and quality of policy development, coordination and enforcement. Launched in 1997, e-Govemment is one of the seven flagship applications listed in Muhimedia Super Corridor (MSC) project. There are a lot of rumors regarding the success and failures of the e-Govemment implementation. Hence, this thesis reveals the success and barriers of the e-Govemment focusing in the eServices flagship application in terms of its regression testing process. The purpose of regression testing is to ensure that changes made to the software, such as adding new features or modifying existing features, have not adversely affected features of the software that should maintenance the same. Although regression testing has been a part of classical computer science literature for decades, the gap between research and practices is so wide that it blocks needed improvement in both environment. Regression testing may be used during development, to test families of similar products or during maintenance to test new or modified configuration. Many methodologies have been reported on how to select regression test so that less problem are occur. As a result, the main purpose of this research is to identifying the methodology that being use in implementing the eServices flagship application. In addition, this research also will be discussed about problems that occur during the regression testing at the eServices flagship application. The following attention of the research will be to identify the best solution to overcome this problem based on the previous situation in terms of technical and also non technical to address them. Perhaps, this research would contribute some idea to the software tester respondents in choosing the accurate methodology and also give an inspiration in terms of solution to defeat problem that occur in the fliture.